2021
DOI: 10.3390/molecules26082285
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Properties In Vitro and Hypoglycaemic Effects of Phenolics from Cultivated Fruit Body of Phellinus baumii in Type 2 Diabetic Mice

Abstract: Dietary intervention in type 2 diabetes mellitus (T2DM) is a hotspot in international research because of potential threats to human health. Phellinus baumii, a wild fungus traditionally used as a food and medicine source, is now cultivated in certain East Asian countries, and is rich in polyphenols, which are effective anti-inflammatory ingredients useful in treatment of T2DM, with fewer side effects than drugs. To examine the hypoglycaemic effects of Phellinus baumii phenolics (PPE), the metabolite profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 41 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…The insulin-mediated IRS1/AKT/FOXO1 signaling pathway is closely related to pancreatic β-cell function, liver glucose metabolism, and the occurrence and development of T2DM ( 26 ). In recent years, the IRS1/AKT/FOXO1 signaling pathway has attracted wide attention as a key link in the pathogenesis and treatment of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…The insulin-mediated IRS1/AKT/FOXO1 signaling pathway is closely related to pancreatic β-cell function, liver glucose metabolism, and the occurrence and development of T2DM ( 26 ). In recent years, the IRS1/AKT/FOXO1 signaling pathway has attracted wide attention as a key link in the pathogenesis and treatment of T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…As medicinal herbs have been widely studied for its anti-inflammatory properties [ 20 , 21 ], we desire to investigate effective medicinal herbs that have potent medicinal properties. Phellinus baumii has long been used as herbal medicine in Asia, particularly China, Korea, and Japan for the treatment of a variety of ailments, including diabetes, hypercholesterolemia, and most notably cancer [ 11 , 22 ]. Earlier studies showed that PBE can block NF- κ B, transcription factor, which is a crucial regulator in the inflammatory cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Phellinus baumii , a wild fungus, has traditionally been used as healthy food or a folk tonic in East Asia because of its multiple physiological functions, including blood lipid level-lowering, antitumor, antiinfluenza, and antioxidation capacities, and DNA damage-protecting, immune-stimulating, and antidiabetic activities [ 11 13 ]. Polysaccharides, polyphenols, and flavonoids, which have a wide spectrum of health benefits and biological activities, have been reported as the principal bioactive ingredients of the Phellinus fungus in modern medical research [ 14 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The general process of studying the Sanghuang species often starts from extracting the desired components. To extract them from the Sanghuang species, the fruiting bodies are typically dried and turned into powder, followed by hot water extraction or ethanol extraction, depending on whether the target material comprises water-soluble polysaccharides or other ethanol-soluble components [ 2 , 4 , 34 , 35 , 36 , 37 ]. These two methods, often assisted by ultrasonic devices, are widely used due to their undeniable advantages: they are cheap and easy to perform [ 2 , 13 , 14 , 21 , 32 , 37 , 38 , 39 , 40 , 41 , 42 ].…”
Section: Introductionmentioning
confidence: 99%